Inculcating Self Correction in Writing through Peer e-Editing - Hassan, Haslina (Common Ground Publishing, 2008)
Peer editing enables students to collaborate and edit each other’s writing. In L2 classroom, the exercise does not only offer distinct advantages to language learning but also encourages students to be more responsible for their own writing. A number of studies have been conducted on the advantages, effectiveness and importance of peer editing in L2 classroom. However, little attention has been given to the hidden values of the exercise. This study reports the positive impact of e-editing works on students of Arabic L2 class as far as grammar is concerned. Both quantitative and qualitative data were obtained and triangulated. The findings showed that, the students were more responsible with their own writing and the quality was improved over the course of one semester.